2001
DOI: 10.2118/01-12-02
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to the Determination of Permeability Tensors for Naturally Fractured Reservoirs

Abstract: The use of permeability tensors is required when modelling fluid flow in anisotropic and heterogeneous reservoirs presenting multiple zones of directional permeability, or those categorized as naturally fractured reservoirs. A general procedure for characterizing complex reservoirs utilizing their permeability tensor is being developed by integrating data and methods from different disciplines. Permeability tensors for geologically defined fracture patterns are derived, and finally these smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Anisotropic permeability of these fractures is often described by a permeability tensor (Oda, 1985), an equivalent continuous method to model fluid flow in petroleum and hydrological studies (Snow, 1969). The permeability tensor in a set of parallel fractures is defined as (Gupta et al, 2001):…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisotropic permeability of these fractures is often described by a permeability tensor (Oda, 1985), an equivalent continuous method to model fluid flow in petroleum and hydrological studies (Snow, 1969). The permeability tensor in a set of parallel fractures is defined as (Gupta et al, 2001):…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…One deficiency of using the permeability tensor is the assumption of infinite fractures (Gupta et al, 2001), which neglects the connectivity of the joint networks.…”
Section: Limitationsmentioning
confidence: 99%
“…1. Although permeability of naturally fractured reservoirs is best described using a nine-component permeability tensor (Gupta et al, 2001;Tran et al, 2004), a simplified form of permeability tensor is commonly acceptable for coals as indicated as follows.…”
Section: Directional Permeability For Coalsmentioning
confidence: 99%
“…A review of these models can be found in the works of [12], [13] and [14] for continuum approach. [15], [16], [17], [18] and [19] for flow through discrete fracture approach.…”
Section: Introductionmentioning
confidence: 99%